2014
DOI: 10.15282/jmes.7.2014.21.0119
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Sugarcane Quality from Juice Samples using Portable Spectroscopy

Abstract: Rapid determination of sugarcane quality using low-cost and portable equipment is more practical for field use. Thus, this study explored the potential application of a portable visible and shortwave near infrared spectroradiometer (VNIRS) to predict pol and brix from sugarcane juice samples. A total of 100 sugarcane juice samples for each clear and raw juice samples were assessed. The spectral data were collected by scanning the juice samples in a cuvette with 10 mm path length using transmittance mode. Parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Mat et al [12] explore the potential of spectroscopic method to predict sugarcane quality parameters by directly scanning the internode samples. Nawi et al ( [7,13]) used visible and shortwave near infrared (Vis/SWNIR) spectroscopy to predict soluble solids content and sucrose content from sugarcane juice samples. The overall results indicated that Vis/SWNIR spectroscopy combined with PLS models could be applied to predict sugar content in both clear and raw sugarcane juices.…”
Section: Introductionmentioning
confidence: 99%
“…Mat et al [12] explore the potential of spectroscopic method to predict sugarcane quality parameters by directly scanning the internode samples. Nawi et al ( [7,13]) used visible and shortwave near infrared (Vis/SWNIR) spectroscopy to predict soluble solids content and sucrose content from sugarcane juice samples. The overall results indicated that Vis/SWNIR spectroscopy combined with PLS models could be applied to predict sugar content in both clear and raw sugarcane juices.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, multiple regression analysis helps us modify the dependent variable when our independent variables are changed. Third, MLR can be applied to predict the future trends and values (Nawi et al, 2014;Zhang et al 2008).…”
Section: Mlrmentioning
confidence: 99%
“…Most studies have applied spectroscopic methods such as NIR to predict the quality of sugarcane in the sugar industry (Nawi et al 2014;Taira et al 2010). In a study, in order to rapidly determine the quality of sugarcane, the potential use of infrared spectrophotometry as well as visible and near-infrared reflectance spectroscopy (VNIRS) were investigated to predict Pol and Brix of raw and refined syrup samples.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…High fiber (>14%) reduces sugar extraction, and low fiber (<11%) encourages lodging and cane pests. Brix content defines the total soluble solids, dissolved sugars and salts including sucrose, reducing sugars, glucose and fructose present in the cane juice (Nawi et al, 2014). It is indefinite indica-tor of sugar content.…”
mentioning
confidence: 99%